2009
DOI: 10.1016/j.jpain.2009.01.242
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid chronic pain and depression: who is at risk?

Abstract: The purpose of this study was to investigate the prevalence and demographic risk factors of chronic pain and its comorbidity with depression. Computer-assisted telephone interviewing was utilized to obtain a representative community sample in the state of Michigan (N = 1,179). The prevalence of chronic pain due to any cause was 21.9%.Approximately 35% of participants with chronic pain also had comorbid depression (7.7% of the entire sample). Depression was not associated with pain types or sites. A multinomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…African Americans have higher levels of comorbid depression and/or anxiety, fear, and helplessness than whites [13,41,67,78] African Americans are more likely to attribute pain to personal inadequacies than whites [58] Overt behavioral expression of pain; verbal expressions; pain reporting; pain coping strategies; healthcare seeking; activity/role interference and restrictions African Americans are more likely than whites to underreport pain unpleasantness, especially in the presence of physicians perceived as ''higher social status'' [52] African Americans and Hispanics are more likely than whites to believe health professionals did not believe them when they reported being in pain [74] African Americans experience greater activity interference at comparable pain level than whites or Hispanics [6,48,50,51,61] African Americans are more likely to use passive pain coping strategies (prayer, pain catastrophizing) [41,92] African Americans and Hispanics are more afraid than whites of opioid addiction risk [3,23] Volume 469, Number 7, July 2011 Racial/Ethnic Disparities in Pain Management 1863 recognized knowledge regarding pain conditions and pain management principles and strategies, especially the pharmacology and prescribing guides for pain medications, are not well covered in medical undergraduate and specialty education. Physicians' lack of such knowledge and the resultant discomfort in pain management skill level have been advanced as important contributors to the observed racial/ethnic disparities [2,13,100].…”
Section: Provider Level Contributorsmentioning
confidence: 99%
“…African Americans have higher levels of comorbid depression and/or anxiety, fear, and helplessness than whites [13,41,67,78] African Americans are more likely to attribute pain to personal inadequacies than whites [58] Overt behavioral expression of pain; verbal expressions; pain reporting; pain coping strategies; healthcare seeking; activity/role interference and restrictions African Americans are more likely than whites to underreport pain unpleasantness, especially in the presence of physicians perceived as ''higher social status'' [52] African Americans and Hispanics are more likely than whites to believe health professionals did not believe them when they reported being in pain [74] African Americans experience greater activity interference at comparable pain level than whites or Hispanics [6,48,50,51,61] African Americans are more likely to use passive pain coping strategies (prayer, pain catastrophizing) [41,92] African Americans and Hispanics are more afraid than whites of opioid addiction risk [3,23] Volume 469, Number 7, July 2011 Racial/Ethnic Disparities in Pain Management 1863 recognized knowledge regarding pain conditions and pain management principles and strategies, especially the pharmacology and prescribing guides for pain medications, are not well covered in medical undergraduate and specialty education. Physicians' lack of such knowledge and the resultant discomfort in pain management skill level have been advanced as important contributors to the observed racial/ethnic disparities [2,13,100].…”
Section: Provider Level Contributorsmentioning
confidence: 99%
“…33 Previous research has suggested that depression and chronic pain are common comorbid conditions and that 1 out of every 3 individuals suffering from chronic pain is estimated to also suffer from depression. 37 Individuals suffering from both conditions are likely to experience greater levels of disease-related burden. 37 For instance, people with orthopaedic pain conditions who are also depressed are at a greater risk of having elevated levels of pain intensity and prolonged work disability compared to those who are not depressed.…”
mentioning
confidence: 99%
“…37 Individuals suffering from both conditions are likely to experience greater levels of disease-related burden. 37 For instance, people with orthopaedic pain conditions who are also depressed are at a greater risk of having elevated levels of pain intensity and prolonged work disability compared to those who are not depressed. 5,37 Increasingly compelling research suggests that elevated levels of depression among individuals with musculoskeletal pain are associated with increased risk for poor response to physical therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on clinical depression has been noted before the effect on the pain. We find that ketamine infusions in NP treatment are particularly effective given the clustering of chronic pain with depression occurs at such a high prevalence, ranging from 30 to 60 % [109][110][111].…”
Section: Clinical Experiencementioning
confidence: 90%